2013
DOI: 10.3758/s13421-013-0371-0
|View full text |Cite
|
Sign up to set email alerts
|

Putting category learning in order: Category structure and temporal arrangement affect the benefit of interleaved over blocked study

Abstract: Recent research in inductive category learning has demonstrated that interleaved study of category exemplars results in better performance than does studying each category in separate blocks. However, the questions of how the category structure influences this advantage and how simultaneous presentation interacts with the advantage are open issues. In this article, we present three experiments. The first experiment indicates that the advantage of interleaved over blocked study is modulated by the structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
221
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 141 publications
(252 citation statements)
references
References 53 publications
28
221
3
Order By: Relevance
“…This result parallels previous evidence (e.g., Shea and Morgan, 1979; Carvalho and Goldstone, 2014a) showing a benefit of blocked study during study. However, this study advantage does not always transfer to an equivalent advantage of blocked study during test.…”
Section: Resultssupporting
confidence: 91%
“…This result parallels previous evidence (e.g., Shea and Morgan, 1979; Carvalho and Goldstone, 2014a) showing a benefit of blocked study during study. However, this study advantage does not always transfer to an equivalent advantage of blocked study during test.…”
Section: Resultssupporting
confidence: 91%
“…Thus, presenting objects that belong to different categories simultaneously, or close in time, can also boost learning (Carvalho & Goldstone, 2014;Gentner & Markman, 1994). In the context of geology instruction, for example, Jee, Uttal, and Gentner (2008) demonstrated that studying two highly similar examples that differ only in terms of the presence of a Bfault^improves learning of that concept.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…For example, in these studies (e.g., Zulkiply and Burt, 2013; Carvalho and Goldstone, 2014), discriminability within and between categories is manipulated by changing number of times (i.e., frequency) that relevant and/or irrelevant category features co-occurred at each category exemplar presentation. These studies have demonstrated that spaced/interleaved schedules promote generalization performance for low-discriminability categories, but perhaps not high-discriminability categories.…”
Section: Discussionmentioning
confidence: 99%